Impacto financeiro de 2010 a 2030 do envelhecimento dos beneficiários em operadoras de plano de saúde de Minas Gerais: um estudo de caso - Beatriz Resende Rios da Mata (2011)
The portfolio aging of individual health plans, combined with epidemiological changes andthe regulatory legislation of the National Health Insurance, is a challenge to be faced by thehealth insurance market. The aim of this dissertation is to analyze what the financial impactover the next 20 years for health insurance carriers would be, if prices do not change. Dataused came from a sample of operators of the type of Medical Cooperative in Minas Gerais,from 2003 to 2009. The method adopted was the cohort-component projections, with twomethodological approaches: 1) fixed rate method, with constant spending per beneficiary,calculating a pure demographic effect, isolated from other factors affecting spending onhealth, 2) method of variable rate variation over the years of spending per beneficiary due tothe change in the price of procedures, combined with the changes of service utilization by thebeneficiaries. For each approach, a number of scenarios were created. The results indicate thatthe proportion of elderly grows up and reaches 26% at the end of 2030; also, losses increaseexponentially over from 2010 to 2030, according to two methods. There is an increasingassociation between the average spending per beneficiary for 59 years or more and up to 18years, exceeding the limit set by six times the monthly SLA between these age groups. In thescenarios of having an estimated initial monthly fee, only to cover health care expenses, andno real increases over the period, the results are worrisome, independent of the method used,due to the reduced timeline (two years) for operators to keep portfolios solvents. In thescenery of initial inclusion of monthly profit and losses are the carriers survive longer, morecomfortable with the method of fixed rate. In alternative scenarios, if the plans were no longermarketed, findings indicate similarities with other scenarios obtained, but the method of fixedrate gains imply some years of relevant financial survival. The contribution of thisdissertation, finally, is to underscore and disentangle the impact yielded by the aging processin the private sector, and to highlight that solutions are urgent to the future solvency of theportfolios.